Diet complementation as a frequency-dependent mechanism conferring advantages to rare plants via dispersal - Morán López, Teresa (2018)
We used an agent-based model to test the hypothesis that diet complementation by frugivores can promote the persistence of rare plant species in communities (DCH). Models simulated bird movement, frugivory, seed dispersal and plant recruitment on landscapes that differed in their degree of fragmentation and in their degree of fruiting species mixing at the scale of frugivores’ foraging decisions. Diet complementation promoted the dispersal of rare species without the need of a priori preference from birds. The effects of landscape structure on the dispersal of rare plants were small (<5%) compared to positive effects of diet complementation because birds tracked the nutrients contained in rare fruits to balance their diets. However, resource-tracking of rare fruits increased foraging costs up to 20% of net energy intakes. During postdispersal stages, density-dependent mortality only conferred advantages to rare plants when located within heterospecific plant patches. Still, thanks to rare-biased dispersal, rare plants showed the highest seed dispersal effectiveness irrespectively of landscape configuration. Our theoretical approach presents a behavioural mechanism by which fruit choice can act as a frequency-dependent mechanism conferring rare species advantages as important as classic postdispersal density-dependent processes. We hope that this study stimulates future work aimed at evaluating the importance of diet complementation in structuring the composition and spatial patterning of plant communities. A plain language summary is available for this article.